Book Reviews (Historia, 2021)
1. Joseph Lehmann: The First Boer War2. Percy M. Clark: The Autobiography of an old Drifter3. E. C. Tabler: James Chapman, Travels in the Interior of South Africa4. D. J. Roorda: Het rampjaar 16725. Marius J. Swart: Wereldleiers